Alternating Multilayer Structural Epoxy Composite Coating for Corrosion Protection of Steel. Issue 12 (18th September 2019) - Zhang, Jiaoxia; Zhang, Weirui; Wei, Liping; Pu, Liuyue; Liu, Jianping; Liu, Hu; Li, Yingchun; Fan, Jincheng; Ding, Tao; Guo, Zhanhu
Abstract: Epoxy composite coatings filled with fillers have been used extensively as anticorrosion materials. In this study, an alternating multilayer structure is designed to obtain multifunctional epoxy resin composite coating based on stepwise coating method via adding graphene and α‐alumina. Their mechanical properties, thermal conductivity, dielectric and anticorrosion properties are characterized. The toughness and the thermal conductivity clearly increase, while the dielectric properties decrease approximately to zero when the filler mass fraction increases from 0.00% to 0.15%. The whole corrosion process is controlled by electrochemical reaction, and the fillers effectively block the corrosive medium, thus improving the anticorrosion performance of the composite coating. Abstract : An alternating multilayer structure is designed to obtain multifunctional epoxy resin composite coatings based on stepwise coating method via adding graphene and α‐alumina. The toughness and the thermal conductivity are clearly increased, while the dielectric properties are decreased when the filler content is increased. The fillers effectively improve the anticorrosion performance of the composite coating.